MiR-9 Regulates the Expression of BACE1 in Dementia Induced by Chronic Brain Hypoperfusion in Rats - Hailong Xie; Ying Zhao; You Zhou; Lin Liu; Yueting Liu; Dongxue Wang; Shuang Zhang; Mingyan Yang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: MicroRNA-9 (miR-9) plays important roles in nervous system diseases such as glioblastoma and neurodegenerative disorders. However, how miR-9 contributes to dementia requires further study. In this study, we evaluated the role of miR-9 in dementia and the molecular mechanisms underlying its effects. Methods: A rat model of dementia was created by occlusion of the bilateral common carotid artery (2VO) for 8 weeks. Learning and memory were assessed using the Morris Water Maze (MWM). MicroRNA expression profiling was performed according to a protocol provided by LC Sciences, and quantitative real-time PCR (qRT-PCR) was used to detect the level of miR-9. Transmission electron microscopy (TEM) and hematoxylin-eosin (HE) staining were used to assess pathological changes in brain tissue. Western blot and immunofluorescence were employed to detect the expression of β-site APP cleaving enzyme 1 (BACE1) and c-AMP response element-binding protein (CREB). Results: Learning and memory were significantly impaired in 2VO rats, and these changes were accompanied by neuronal loss and glial activation in brain tissues. miR-9 was greatly upregulated in both the hippocampus and cortex of rats following 2VO. Knockdown of endogenous miR-9 via lentiviral vector-mediated delivery of its antisense molecule (lenti-pre-AMO-miR-9) reduced the vulnerability to dementia, reversed the increase in BACE1 expression, and ameliorated the reduction in CREB expression triggered by 2VO. BACE1 protein levels were significantly increased, but CREB protein levels were significantly decreased in the presence of miR-9 in cultured neonatal rat neurons (NRNs). AMO-miR-9 rescued the upregulation of BACE1 and downregulation of CREB elicited by miR-9 in rats. Dual luciferase assay experiments showed that overexpression of miR-9 inhibited the expression of CREB by targeting its 3’UTR domain. CREB protein was downregulated by miR-9 overexpression which was reversed by miR-9 inhibition in cultured NRNs. TEM imaging showed that miR-9 caused damage to NRNs, which was reversed by addition of AMO-miR-9. Conclusion: We conclude that miR-9 plays an important role in regulating the process of dementia induced by 2VO in rats by increasing BACE1 expression via downregulation of CREB.